2020
DOI: 10.3390/genes11111238
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel de Novo Variant in the SYT2 Gene Causing a Rare Type of Distal Hereditary Motor Neuropathy

Abstract: Objective: To report the first de novo missense mutation in the SYT2 gene causing distal hereditary motor neuropathy. Methods: Genetic testing was carried out, including clinical exome sequencing for the proband and Sanger sequencing for the proband and his parents. We described the clinical and electrophysiological features found in the patient. Results: We reported a proband with a new de novo missense mutation, c.917C>T (p.Ser306Leu), in the C2B domain of SYT2. The clinical presentation was similar to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Notably, a pathogenic variant has been found at the residue corresponding to Ser309 in the homologous SYT2 . 25 In the Ca 2+ -bound simulations, both Met303Val and Ser309Pro increased the mobility of the distal arginine apex (Arg399, Arg400) at the opposite end of the C2B domain ( Supplemental Figure 4 ).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Notably, a pathogenic variant has been found at the residue corresponding to Ser309 in the homologous SYT2 . 25 In the Ca 2+ -bound simulations, both Met303Val and Ser309Pro increased the mobility of the distal arginine apex (Arg399, Arg400) at the opposite end of the C2B domain ( Supplemental Figure 4 ).…”
Section: Resultsmentioning
confidence: 92%
“…Novel variants may exert dominant-negative effects, as seen for previously identified variants, 10 , 8 , 9 but we cannot preclude haploinsufficiency as a possible pathogenic mechanism. Ca 2+ -binding loops 1 and 3 of the C2B domain seem to be highly sensitive to variation as pathogenic missense variants cluster in these regions in both SYT1 and the homologous SYT2 , 25 , 33 , 34 and no missense SYT1 variants in these loops are recorded in the Genome Aggregation Database version 2.1.1. 22 Therefore, any de novo missense variant in the C2B Ca 2+ -binding loops should be investigated for possible pathogenicity, and variants in other highly conserved residues of the SYT1 C2 domains should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Heterozygous mutations in the SYT2 gene have been recently reported in patients presenting as a motor neuropathy from three unrelated families with a dominant pattern of inheritance 4,8,9 and from a case of de novo mutation without electrophysiological alterations. 10 The first reported variants were two missense mutations affecting consecutive residues within the calcium-binding pocket of the C2B domain of SYT2 protein, p.Asp307Ala, and p.Pro308Leu. 4 This domain seems to be the key driver synaptic vesicle fusion, [11][12][13] Figure 1C) and are expected to be particularly affected by the introduction of a lysine at position 371.…”
Section: Discussionmentioning
confidence: 99%
“…4,8,9 It deserves to be mentioned that the lack of electrophysiological alteration in the patient described is a 10-years-old male, and it could be related to the young age. 10 However, electrophysiological studies also revealed findings indicating a presynaptic NMJ defect, 13. Yoshihara M, Guan Z, Littleton JT.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several SYTs are linked more loosely to pathogenesis in neurological disorders arising from other primary causes. The first mutations identified in human SYTs were found in the SYT2 C2B domain in patients presenting with non-progressive peripheral motor neuropathies with unusual similarities to Lambert–Eaton myasthenic syndrome (LEMS) [ 189 , 190 , 340 , 341 ]. LEMS is an autoimmune disorder commonly linked to auto-antibodies against the presynaptic Ca 2+ channel that disrupt NMJ function [ 342 ].…”
Section: Relevance Of Synaptotagmin Dysfunction To Human Diseasementioning
confidence: 99%